Gums and stabilisers for the food industry - Williams, Peter A.; Phillips, Glyn O.; Morris, V. J. (Royal Society of Chemistry, 1998)
This work contains the proceedings of a conference on gums and stabilisers for the food industry. Contributions are concerned with the structure-function relationships of various polysaccharides and protein systems, as well as progress on mixed biopolymer systems.